Nilai-Nilai Kearifan Lokal Pada Wacana Ritual Adat “Helas Keta” Etnik Atoni Pah Meto: Kajian Etnolinguistik - Feka, Viktorius P.; Agnes M.D. Rafael (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
This study aims to reveal the values of local wisdom of the Atoni Pah Meto Ethnic in the discourse of the traditional ritual “Helas Keta’ in Timor Island, East Nusa Tenggara, based on an ethnolinguistic perspective. This research employs qualitative-descriptive method. This research is conducted in the three stages namely data collection, data analysis, and data analysis display. The results of the study show that the traditional ritual "Helas Keta" contains various local wisdom values. These local wisdom values ??appear in linguistic units through the local language of the Atoni Pah Meto ethnic group, namely Uab Meto, which is used by the Atoni Pah Meto ethnic group to communicate. Besides, there are two forms of local wisdom, namely tangible local wisdom and intangible local wisdom. As such, tangible local wisdom containing noble values ??consists of reed leaves, sticks, stones and water, sacrificial animals, woven bags and betel nut, and tuak. Intangible local wisdom encompasses parable and advice. The values ??of local wisdom contained in the ritual “Helas Keta” are job description, recognition, kinship and brotherhood strengthening, cooperation and mutual respect, wisdom and justice, confession and repentance, reconciliation, self-purification, love, true peace.